Ethnicised entitlements? Property rights and civil war in Sri Lanka - Benedikt Korf (University of Bonn, Center for Development Research (ZEF), 2003)
The present paper investigates how ethnic violence and civil war in Sri Lanka have affected local property rights institutions . I use local case studies to analyze the institutional relations and alliances between civilians and combatants in the emergent society of violence that shapes local communities in civil war. My focus will be on how civilians from different ethnic groups utilize social and political capital assets to secure entitlements to natural resources. The findings of my research suggest that resource entitlements in Trincomalee are ethnicised in the sense that opportunities and access to resources are unequally distributed among the three ethnic groups (Sinhalese, Tamils, Muslims), because these groups are unequally endowed with political capital. Patron-client networks based on ethnicity shape the relative bargaining power of local actors. This system reproduces perceived grievances among the different ethnic groups and thus reproduces the conditions for ethnic violence.
Keywords: 330; Political Economy; Resource /Energy Economics and Policy; Eigentumsrecht; Agrarverfassung; Ethnische Diskriminierung; Bürgerkrieg; Sri Lanka